Chitosan – poly(butylene succinate) scaffolds and human bone marrow stromal cells induce bone repair in a mouse calvaria model - Costa-Pinto, A. R. (2012)
Tissue engineering sustains the need of a three-dimensional (3D) scaffold to promote the regeneration of tissues in volume. Usually, scaffolds are seeded with an adequate cell population, allowing their growth and maturation upon implantation in vivo. Previous studies obtained by our group evidenced significant growth patterns and osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs) when seeded and cultured on melt-based porous chitosan fibre mesh scaffolds (cell constructs). Therefore, it is crucial to test the in vivo performance of these in vitro 3D cell constructs. In this study, chitosan-based scaffolds were seeded and cultured in vitro with hBMSCs for 3 weeks under osteogenic stimulation conditions and analysed for cell adhesion, proliferation and differentiation. Implantation of 2 weeks precultured cell constructs in osteogenic culture conditions was performed into critical cranial size defects in nude mice. The objective of this study was to verify the scaffold integration and new bone formation. At 8 weeks of implantation, scaffolds were harvested and prepared for micro-computed tomography (μCT) analysis. Retrieved implants showed good integration with the surrounding tissue and significant bone formation, more evident for the scaffolds cultured and implanted with human cells. The results of this work demonstrated that chitosan-based scaffolds, besides supporting in vitro proliferation and osteogenic differentiation of hBMSCs, induced bone formation in vivo. Thus, their osteogenic potential in orthotopic location in immunodeficient mice was validated, evidencing good prospects for their use in bone tissue-engineering therapies.